Winds vs. tides: Factors ruling the recruitment of larval and juvenile fishes into a micro-tidal and shallow choked lagoon (Argentina) - Bruno, Daniel Osvaldo (2015)
Choked lagoons (like Mar Chiquita, Argentina) are influenced by local winds because the inlet channel acts as a dynamic filter which reduce tidal fluctuations. Previous studies showed that the effects of onshore winds appear to prevail over daily-tide cycles (ebb, flood) in the recruitment of young fishes into this micro-tidal and shallow estuary. Therefore, the aim of this study was to evaluate the recruitment success of larval and juvenile fishes from the sea into this choked lagoon related to the conjunction of global (lunar-tide cycle) and local (wind regime) processes. Weekly fish sampling was conducted in Mar Chiquita’s inlet channel and its adjacent surf zone from early spring to late summer. For each fish developmental stage (i.e. larval and juvenile), a multiple-hypothesis model approach was adopted by fitting generalized linear models (GLM) with the abundance of fishes as the response variable and possible combinations of seasons, sites, water parameters and the wind effect as explanatory variables. The abundances of fish larvae and juveniles were mainly affected by wind regimen and seasonal changes according to the best model selected. Larval and juvenile fishes were more abundant at summer months during strong (> 10 m · s−1) onshore wind episodes. The lunar-tide cycle effect was not relevant for the success of fish recruitment. Despite its seasonal regularity, wind is a much more unpredictable factor than tides, and therefore, it is remarkable to note the implications that have for fishes the recruitment towards an estuarine system depending on such unpredictable force. The importance of the fish nursery role of the coastal area close to the mouth of an estuary with this environmental feature is discussed.